Detection and Analysis of Radiation Doses in Multiple Orbital Space during Solar Minimum - Juyu Wang; Shenyi Zhang; Guohong Shen; Ying Sun; Binquan Zhang; Zheng Chang; Chunqin Wang; Donghui Hou; Zhe Yang (Aerospace, 2023)
Based on orbit detection data acquired by a positive channel Metal Oxide Semiconductor (PMOS) dose detectors on FY4-A (GEO), BD3-M15 (MEO), and YH1-01A (LEO) between November 2018 and November 2022, investigations reveal variations in total dose and the mechanism of radiation dose increase within the geostationary earth orbit (GEO), medium earth orbit (MEO), and low earth orbit (LEO) during the transition from the 24th to the 25th solar cycles. It provides the radiation dose parameters for the study of the space environment from different altitude orbits, and also provides an important basis for studying the solar minimum activity and dose generation The data indicate directional disparities in radiation doses among the orbital regions, with the hierarchy being FY4-A > YH1-01A > BD3-M15. Furthermore, the results show that the total doses of FY4-A and BD3-M15 were higher than that of YH1-01A by two orders of magnitude, with BD3-M15 > FY4-A > YH1-01A. The monthly radiation dose rates of FY4-A in GEO and BD3-M15 in MEO exhibited positive correlation with their corresponding APs during the solar minimum. Notably, for FY4-A, the monthly radiation dose rate during geomagnetic disturbed periods exceeded that of the dose rate during geomagnetic quiet periods by one order of magnitude. This analysis revealed the substantial impact of geomagnetic storms and space environment disturbances on radiation doses detected by MEO and GEO orbital satellites. These perturbations, attributable to medium- and small-scale high-energy electron storms induced by reproducible coronal holes, emerged as key driving factors of the increase in radiation doses in MEO and GEO environments.